Hotspots of Subterranean Biodiversity - Pipan, Tanja; Culver, David C.; Deharveng, Louis (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
There are a total of 22 caves and karst wells with more than 25 specialized species resident (stygobionts and troglobionts). In this Special Issue, 14 of these sites are described in detail, along with the specialized fauna. An additional paper describes the richest known cave in China. A summary paper puts all 22 subterranean biodiversity sites in context.